2022
DOI: 10.1002/smmd.20220012
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial infection microenvironment‐responsive porous microspheres by microfluidics for promoting anti‐infective therapy

Abstract: The overuse of antibiotics for treating bacterial infection has caused severe bacterial resistance and become a public health threat worldwide. It is desired to develop novel antibiotic delivery systems as efficient antibacterial strategies for promoting anti‐infective therapy. Herein, the AgNPs‐loaded N‐[(2‐hydroxy‐3‐trimethyl ammonium) propyl] chitosan (HTCC)/hyaluronic acid (HA) porous microspheres (HHPMs) by microfluidics have been developed as novel bacterial infection microenvironment (IME)‐responsive an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(48 citation statements)
references
References 48 publications
0
48
0
Order By: Relevance
“…Since PFC liquid features a low boiling point, microfluidic technology allows a moderate fabrication process, thus realizing the maintenance of the physiochemical properties of PFC. 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 Ascribed to the US-induced phase-transition ability of PFCs, the PO/GI-MCs experienced the transition from microcapsules to microbubbles when exposed to US waves (1.0 MHz, 1.2 W cm −2 ). Since the volume of PFCs can become five times larger, the resultant gas core splits the alginate shell, releasing the gas, which contains a large amount of oxygen.…”
Section: Us-responsive Matters and Potential Applicationsmentioning
confidence: 99%
“…Since PFC liquid features a low boiling point, microfluidic technology allows a moderate fabrication process, thus realizing the maintenance of the physiochemical properties of PFC. 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 Ascribed to the US-induced phase-transition ability of PFCs, the PO/GI-MCs experienced the transition from microcapsules to microbubbles when exposed to US waves (1.0 MHz, 1.2 W cm −2 ). Since the volume of PFCs can become five times larger, the resultant gas core splits the alginate shell, releasing the gas, which contains a large amount of oxygen.…”
Section: Us-responsive Matters and Potential Applicationsmentioning
confidence: 99%
“…The process of wound healing can be divided into three stages, which include inflammatory, proliferative, and remodeling. In the early and entire phase of inflammation, the accelerated recruitment of cytokines and immune cells is very important. It has been shown that endogenous electric fields can promote the migration of macrophages, lymphocytes, and neutrophils to skin wound sites and ultimately promote wound healing .…”
Section: Applying Tengs-based Es For Promoting Wound Healingmentioning
confidence: 99%
“…In recent years, more and more pathogenic superbugs have become resistant to antibiotics, posing a serious threat to human health resulting from their misuse. , Of the many prevalent antibiotic-resistant bacterial strains, methicillin-resistant Staphylococcus aureus (MRSA) arouses the scientific community’s interest because of its ability to evade antibiotic treatments and trigger clinical infections that are difficult to treat. , With the emergence of a mecA gene in MRSA, bacteria have acquired resistance to beta-lactam antibiotics such as methicillin through the expression of an insensitive penicillin-binding protein (PBP2a) . The beta-lactam antibiotics can combine with PBP inhibiting the activity of PBP, which is responsible for peptidoglycan synthesis in the cell membrane during cytokinesis .…”
Section: Introductionmentioning
confidence: 99%